Development Of Animated Video Media For Beginning Reading Of Grade I Students In Elementary School - Ciana Aning Putri; Zaka Hadikusuma Ramadan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Beginning reading activities have always been taught since elementary education in grade 1. However, not all students have the ability to read from the start of elementary school. Because every student has a different background and condition when they enter elementary school. Therefore, initial reading skills need to be redeveloped through teaching that is implemented with learning models and media presented by teachers or educators. When reading, the eyes will recognize the word while the mind connects it with its meaning. In order t o create good relations between educators, students and parents of students. preparation of learning objectives is very important in the series of learning design development. At this stage, the teacher will determine the learning objectives that become a reference for determining the type of learning materials, learning strategies, learning methods, and learning media that will be used in the learning process. Learning materials can not only be channeled through material books, but the development of learning media in this 2-dimensional form can also be an innovation in developing models and teaching materials in class. The results showed that learning activities in class I still used simple media in reading activities. Not all students have the ability to read the beginning. Animated videos for beginning reading are appropriate for use in classroom learning activities.